Evaluasi Kepuasan Pembangunan Infrastuktur Jalan di Kota Dumai - Wulan Indriyani; Yuli Anggraini; Nadila Syauqinah; Geri Rizki Permana; Ilham Rahmany (UIN Imam Bonjol Padang, 2022)
Infrastructure development is one of the fundamental elements to accelerating regional and national growth. The government is in charge of infrastructure development as a way to give the residents of Dumai City the best services possible. Infrastructure like transportation, telecommunications, sanitation, and energy availability cannot be isolated from a country's or region's rate of economic growth and investment. It also has a significant impact as one of the forces driving economic expansion, which is the cornerstone of long-term economic prosperity. This study aims to gauge community satisfaction with the current road infrastructure in Dumai City in addition to bringing the Dumai City Government's attention to damaged road infrastructure. Data was gathered using a Google form-based smartphone application, and IBM SPSS Statistics version 26 was used for analysis. For the research sample in this study, 100 samples of respondents were chosen. Due to the Dumai City Government's lack of attempts to repair damaged roads, the community is dissatisfied with the road infrastructure, according to the study's findings.